Adherence in a pavement rehabilitated with a polymeric grid used as interlayer - Delbono, Héctor Luis (2014)
A polymeric grid was placed between layers of a pavement with the aim of preventing the reflection of cracks from the base material to the upper layer. Results explain why the usual faults that occur in rehabilitated pavements: (i) chemical modifications of geosynthetic polypropylene determined by FTIR lead to changes in its melting point; (ii) the discontinuity or continuity of the interface observed by SEM depends on the application temperature of the asphalt mix and (iii) the adherence obtained in laboratory tests correlates perfectly with the quoted chemical modifications of geosynthetic polypropylene and the structure of interface in multilayer pavements.